1997
DOI: 10.1021/bi971136l
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine and Tryptophan Structure Markers in Hemoglobin Ultraviolet Resonance Raman Spectra:  Mode Assignments via Subunit-Specific Isotope Labeling of Recombinant Protein

Abstract: Phenyl-deuterated tyrosine (Tyr-d4) and indole-deuterated tryptophan (Trp-d5) have been selectively incorporated into hemoglobin (Hb) by expressing the gene in auxotrophic strains of Escherichia coli. Ultraviolet resonance Raman (UVRR) spectra, using 229-nm excitation, show that difference features characteristic of the Hb quaternary R --> T transition are not perturbed by the incorporation of the isotopes. All the UVRR bands between 800 and 1700 cm-1 are assigned to either Tyr or Trp except for the 1511 cm-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
144
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(164 citation statements)
references
References 57 publications
19
144
1
Order By: Relevance
“…UVRR difference spectra of hemoglobins typically exhibit two categories of change (37,40,41,42). The first can readily be attributed to quaternary structure-based differences in the ␣ 1 ␤ 2 interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVRR difference spectra of hemoglobins typically exhibit two categories of change (37,40,41,42). The first can readily be attributed to quaternary structure-based differences in the ␣ 1 ␤ 2 interface.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet Resonance Raman Spectroscopy-UVRR spectroscopy of hemoglobins site selectively probes the aromatic residues of the globin domains (35)(36)(37) (35)(36)(37). When the spectra are normalized at the nitrate internal standard as shown (Fig.…”
Section: Front-face Fluorescencementioning
confidence: 99%
“…1 A band of HbA at 1511 cm 1 , which is suggested to be related to Trp, is shifted to a higher frequency by 5 cm 1 in D 2 O. 39 This band has been noted as a quantitative T-specific indicator of HbA. 45 …”
Section: Tryptophan-related Modesmentioning
confidence: 97%
“…6 An analog of Trp with deuterated ring carbons, Trp-2,4,5,6,7-d 5 (Trp-d 5 ), is sometimes used to label Trp residues in peptides and proteins. [23][24][25][26][27] The deuteration has little affect on the vibrational mode of W3 and the wavenumber of the corresponding vibration of Trp-d 5 (Wd3) also changes with | 2,1 | in a way similar to that of W3.…”
Section: Conformation Markermentioning
confidence: 99%
“…5,23 In UV resonance Raman spectra excited at 229 nm, the W4 band can be detected but the W6 band is not clear. 27,38,39 The wavenumbers of the Wd4 (Ϸ1445 cm Ϫ1 ) and Wd5 (Ϸ1405 cm Ϫ1 ) bands of Trp-d 5 also depend on hydrogen bonding in a way similar to that of the W4 and W6 bands of Trp. 8 The Wd4 and Wd5 bands are detectable in 229-nm excited Raman spectra 27 and may be useful in studying the Adapted from the data of Miura et al 5 The atomic displacements in the two vibrations are also shown.…”
mentioning
confidence: 96%